2017
DOI: 10.1007/s00223-017-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of the Effects of the Antiretroviral Drugs Stavudine, Tenofovir and the Combination Lopinavir/Ritonavir on Bone Metabolism in a Rat Model

Abstract: Antiretroviral (ARV) treatment may induce metabolic complications in HIV patients on long-term therapy that can affect bone health. In this study, the effects of the ARVs Stavudine (d4T), Tenofovir (TDF) and Lopinavir/ritonavir (LPV/r) on bone metabolism and lipodystrophy were directly compared in rats to negate the consequences of HIV-associated confounding factors. Healthy 12-14-week-old male Wistar rats (n = 40) were divided into four treatment groups and received an oral animal equivalent dose of either St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…In a study of rats, a relatively short exposure to stavudine (nucleoside reverse transcriptase inhibitors) monotherapy and TDF significantly decreased femoral BMD; this translated to decreased bone strength. (36) This finding is similar to our finding that, even in the absence of HIV infection, tenofovir diminished BMD and trabecular bone. In this same rat study, Conradie and colleagues also observed that treatment with both stavudine and TDF resulted in significant marrow adiposity and suggested that osteoblast numbers may be depleted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a study of rats, a relatively short exposure to stavudine (nucleoside reverse transcriptase inhibitors) monotherapy and TDF significantly decreased femoral BMD; this translated to decreased bone strength. (36) This finding is similar to our finding that, even in the absence of HIV infection, tenofovir diminished BMD and trabecular bone. In this same rat study, Conradie and colleagues also observed that treatment with both stavudine and TDF resulted in significant marrow adiposity and suggested that osteoblast numbers may be depleted.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of rats, a relatively short exposure to stavudine (nucleoside reverse transcriptase inhibitors) monotherapy and TDF significantly decreased femoral BMD; this translated to decreased bone strength . This finding is similar to our finding that, even in the absence of HIV infection, tenofovir diminished BMD and trabecular bone.…”
Section: Discussionsupporting
confidence: 88%
“…( 36 , 37 ) However, data from preclinical models have been more mixed. For example, both Conradie et al ( 38 ) and Matuszewsaka et al ( 23 ) noted bone loss with TDF treatment in rats, but neither detected elevated bone resorption marker levels. The reason for this discrepancy is unknown but has been noted in the clinic as well, with direct tissue assessments of bone biopsies from PLWH initiating TDF-based cART showing increased osteoclast surfaces with no corresponding change in CTX levels.…”
Section: Discussionmentioning
confidence: 98%
“…The safety and efficacy of antiretroviral drugs have been monitored, as has the metabolic alteration during the treatment period tested in preclinical trial studies. 13 16 Conradie et al 13 examined the effects of ART on bone metabolism and lipodystrophy in rats. Stavudine (6.2 mg/kg), tenofovir DF (26.6 mg/kg), lopinavir/ritonavir (70.8 mg/kg), and water (1.5 mL) were subjected orally to 40 male rats for 9 weeks.…”
Section: Methodsmentioning
confidence: 99%